1991
DOI: 10.2331/suisan.57.585
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of early growth history in the Japanese sandish with otolith microstructure.

Abstract: Early growth of the hatchery-reared Japanese sandfish Arctoscopus japonicus was deduced by analyzing the otolith microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Accumulation of the basic data about the biology of the larvae and juveniles is important in order to develop these techniques. Some information on growth, otolith daily increment, morphological development and feeding of the larvae and juveniles have been reported 5–9 . This paper reports the fish size and morphological features of reared Japanese sandfish at the onset of burying themselves in the sand under experimental conditions.…”
Section: Frequency Distribution Of Standard Length Of the Japanese Samentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of the basic data about the biology of the larvae and juveniles is important in order to develop these techniques. Some information on growth, otolith daily increment, morphological development and feeding of the larvae and juveniles have been reported 5–9 . This paper reports the fish size and morphological features of reared Japanese sandfish at the onset of burying themselves in the sand under experimental conditions.…”
Section: Frequency Distribution Of Standard Length Of the Japanese Samentioning
confidence: 99%
“…Some information on growth, otolith daily increment, morphological development and feeding of the larvae and juveniles have been reported. [5][6][7][8][9] This paper reports the fish size and morphological features of reared Japanese sandfish at the onset of burying themselves in the sand under experimental conditions. Fertilized eggs were obtained from the Akita Prefectural Fisheries Promoting Center on 15 December 1998.…”
mentioning
confidence: 99%
“…Many studies have used otolith increment widths as estimators of daily growth rate histories (Brothers & McFarland, 1981;Wilson & Larkin, 1982;Volk et al, 1984;Thorrold & Williams, 1989;Tsukamoto et al, 1991). In contrast, other studies have shown an uncoupling of otolith growth and somatic growth rates (Marshall & Parker, 1982;Wright et al, 1990;Mugiya & Tanaka, 1992;Francis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…, 개 체군 분석 (Okiyama, 1970), 이석미세구조를 통 한 초기성장 추정 (Tsukamoto et al, 1991), 일본 나나오만과 토야만에서 부화 방류된 도루묵의 성장, 성숙과 회유 (Tomoda et al, 2006) 등 많은 연구가 꾸준히 진행되어 있으며, 우리나라에서 는 도루묵의 연령·성장과 성숙 (Choi et al, 1983, Yang et al, 2008, 인공종묘 초기사육 (Baik et al, 1989), 난발생 및 치어의 형태 (Myoung et al, 1989), 성성숙과 산란 (Lee et al, 2006), 산란용 조림초 개발 (Yang et al, 2009) 등 이 수행되었다. 또한 에너지수지에 관한 연구로 국내에서는 조피볼락 자치어 (Chin et al, 1998), 물가자미 (Lee et al, 2003), 참가자미 (Park, 2007) 등이 있고, 국외에서는 브라운송어, Salmo trutta (Elliott, 1976), 틸라피아 (Moronova, 1976), 무지개송어 (Staples and Nomura, 1976), 명태 (Kitchell et al, 1977), 노란농어, Perca flavescens (Mills and Forney, 1981)등이 수행되었으나, 도 -129-수온과 먹이에 따른 도루묵 (Arctoscopus japonicus) 치어의 에너지수지 efficiency estimated NT-NA, NT-EA, HT-NA and HT-EA were represented as 75.…”
unclassified